Implementation of "Three Simultaneities" for Occupational Health Protection Facilities in Laboratory Animal Institution Construction Project - CAI Mengshi; SU Xing; SHAO Qiming (Shiyan dongwu yu bijiao yixue)
Occupational health is a discipline dedicated to the identification, assessment, prediction, and control of occupational hazards in the workplace and their potential impacts on health. Its core objective is to ensure the safety of workers through targeted preventive strategies and protective mechanisms, thereby minimizing health risks caused by occupational hazards and promoting physical health, mental well-being, and overall social welfare in the workplace. The "three simultaneities" of occupational health protection facilities in construction projects (hereinafter referred to as "three simultaneities") refers to the principle that occupational disease prevention facilities must be designed, constructed, and put into operation simultaneously with the main project. The implementation of "three simultaneities" involves several stages: a preliminary assessment of occupational disease risks, the design of occupational disease protection facilities in accordance with relevant standards, and ensuring these facilities are constructed in parallel with the primary engineering project to maintain integrity and effectiveness. During the construction phase, occupational disease prevention facilities must be constructed simultaneously with the main project to ensure their integrity and effectiveness. Upon project completion, the construction unit is responsible for evaluating the control effects of occupational disease hazards and conducting the acceptance of occupational disease prevention facilities to ensure the occupational health of employees. The implementation of the "three simultaneities" for occupational disease protection facilities in construction projects is a mandatory national regulation, and non-compliance may result in legal penalties such as fines and forced suspension of work. However, for some laboratory animal institutions, the implementation of the "three simultaneities" remains a challenge. This paper aims to provide practical guidance and feasible implementation strategies for such institutions by introducing the development history of the "three simultaneities" in occupational health, explaining its relevance and necessity in the context of laboratory animal facilities, and outlining step-by-step procedures for compliance and implementation.